Regulating the blink: Cognitive reappraisal modulates attention - Adam, Ruth; Schönfelder, Sandra; Forneck, Johanna; Wessa, Michèle (Frontiers in Psychology, 2014)
Our brain is unable to fully process all the sensory signals we encounter. Attention is the process that helps selecting input from all available information for detailed processing and it is largely influenced by the affective value of the stimuli. This study examined if attentional bias toward emotional stimuli can be modulated by cognitively changing their emotional value. Participants were presented with negative and neutral images from four different scene-categories depicting humans (“Reading”, “Working”, “Crying” and “Violence”). Using cognitive reappraisal subjects decreased and increased the negativity of one negative (e.g., “Crying”) and one neutral (e.g., “Reading”) category respectively, whereas they only had to watch the other two categories (e.g., “Working” and “Violence”) without changing their feelings. Subsequently, subjects performed the attentional blink paradigm. Two targets were embedded in a stream of distractors, with the previously seen human pictures serving as the first target (T1) and rotated landmark/landscape images as the second (T2). Subjects then reported T1 visibility and the orientation of T2. We investigated if the detection accuracy of T2 is influenced by the change of the emotional value of T1 due to the reappraisal manipulation. Indeed, T2 detection rate was higher when T2 was preceded by a negative image that was only viewed compared to negative images that were reappraised to be neutral. Thus, more resources were captured by images that have been reappraised before, i.e., their negativity has been reduced. This modulatory effect of reappraisal on attention was not found for neutral images. Possibly upon re-exposure to negative stimuli subjects had to recall the previously performed affective change. In this case resources may be allocated to maintain the reappraised value and therefore hinder the detection of a temporally close target. Complimentary self-reported ratings support the reappraisal manipulation of negative images.